Book Publishing Patterns in Social Sciences and Humanities in Lithuania: Analysing Trends in DB “Lituanistika” - Gedutis, Aldis; Kirtiklis, Kęstutis; Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2021)
The aim of this article is to reconstruct and analyse scholarly book (or monograph) publication patterns in Lithuanian Social Sciences and Humanities (SSH) registered in national database “Lituanistika”. Database “Lituanistika” provides a good starting point and repository of empirical data as it indexes and abstracts different types of scholarly publications in SSH, monographs included. The empirical part of the research consists of finding registered monographs, attributing them to the individual SSH disciplines, comparing the number of monographs and scholarly articles in various SSH, and retracing the timeline of registered monographs across different disciplines etc. The analytical approach of our research is based on an idea of (social) constructivism. We aim at reconstructing the motives behind the publishing of scholarly books or abstaining from such practice. In this article we argue that the motives to publish (or not to publish) a scholarly book are a product of a broader Lithuanian social, institutional and disciplinary context, which influences and regulates the actions of individual SSH researchers.